Sustainability in the Hospitality Sector: Leveraging Development Value as a Mediating Variable - Pamuji Gesang Raharjo; Parlagutan Silitonga; Anti Ruslan Darawanti; Murpin Sembiring (Universitas Negeri Semarang, 2026)
Amidst the recent challenges the declining hospitality industry faces, this study focuses on enhancing employer branding sustainability in the hotel sector post the COVID-19 pandemic. The research targets hotel employees who have graduated from hospitality vocational schools and colleges. Utilizing Partial Least Squares Structural Equation Modeling (PLS-SEM) analysis, the results highlight the pivotal role of Development Value as a mediator in promoting sustainability within the hotel industry. This underscores the critical importance of hotel management in prioritizing the cultivation and recognition of development value among employees, where management of hotels can effectively enhance their sustainability practices. Inclusion of Development Values as a mediator is a novelty of this research. Employee development is the core that affects the sustainability of employer branding, and it is a strategic step to improve employer branding. Improvements were made to increase the fluency of sentences, consistency in the use of terms, and to clarify some parts to make them easier to understand